Qu’y a-t-il de politique dans les indicateurs écologiques? - Gabrielle Bouleau; Philippe Deuffic (VertigO)
Ecological indicators are widely used to support public action. Their proliferation requires critical appraisal of their normative framing. This article deploys a conceptual framework to reveal their underlying assumptions and worldviews through the critical exploration of the controversies raised during their making and use. It consists in focusing on processes of categorizing and quantifying the environment. Ecological indicators are simplified representations of reality. As such, they constitute social conventions which unite environmental realities existing in specific time and places, while excluding others. We study how they align or confront political constructions of territories or advocacy coalitions in relation to the causal relations they support and the scale at which they are built. We assess whether their ecological framing has become a resource for political framing. We question how far financial considerations and practical use have constrained the making and the use of indicators, with specific attention paid to path dependence from existing data. This article concludes by introducing the other contributions of this volume, by specifying how each one relates to the political appropriation of one or more designing steps of an ecological indicator, to the advantage of existing indicators, and to the effects of ecological indicators in policies.